The Notion of Rationality in Donald Davidson (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
Rationality in Donald Davidson is manifested in acting, speaking and interpreting. Rationality in this sense has two aspects: logical or linguistic and externalist or causal. The first aspect of rationality is expressed byDavidsonian Principle of Coherence, which says that every rational creature has relatively coherent net of propositional attitudes. The principle is used in the process of interpreting human utterances and actions, when the interpreter ascribes propositional attitudes to a speaker or to an agent. The second aspect of rationality is connected with causal history of language acquisition and is expressed by the Principle of Correspondence. As uttered words and human actions are causal effects of events in the external world, a rational creature, i.e. a creature possessing a verbalized knowledge of the world, a first-person knowledge of its propositional attitudes, and a third-person knowledge of propositional attitudes of other rational creatures, must have undergone a causal process of interactions with the reality and other rational creatures. Davidson called this process a “triangulation”.